Energy Systems and Environment 2018
DOI: 10.5772/intechopen.74039
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemical Systems for Energy Valorization of Waste Streams

Abstract: Bioelectrochemical systems (BES) encompass a group of technologies derived from conventional electrochemical systems in which the electrodic reactions are directly or indirectly linked to the metabolic activity of certain types of microorganisms. Although BES have not yet made the leap to the commercial scale, these technologies hold a great potential, as they allow to valorize different liquid and gas waste streams. This chapter is devoted to exploring some of the possibilities that BES offer in the managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…BES are also capable of utilising a broad range of organic and inorganic substrates [2] which gives them a great operational flexibility. Despite that, and despite the numerous scale-up endeavours reported in the literature [3], BES are far from being a mature technology [4]. The still low current densities, relatively large capital cost and the difficulties associated with energy harvesting/management are often reported as major challenges in their way towards practical application.…”
Section: Introductionmentioning
confidence: 99%
“…BES are also capable of utilising a broad range of organic and inorganic substrates [2] which gives them a great operational flexibility. Despite that, and despite the numerous scale-up endeavours reported in the literature [3], BES are far from being a mature technology [4]. The still low current densities, relatively large capital cost and the difficulties associated with energy harvesting/management are often reported as major challenges in their way towards practical application.…”
Section: Introductionmentioning
confidence: 99%
“…The most common configurations of BESs are microbial fuel cells (MFCs) and microbial electrolysis cells (MECs) [6]. As MECs are able to recover valuable hydrogen gas rather than electricity, it has been suggested that scaling up an MEC is more economically viable than scaling up an MFC [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…BES are also capable of dealing with a broad range of organic and inorganic substrates [2] which gives them a great operational flexibility. Despite that, and despite the numerous scale-up experiences reported in the literature [3], BES are far from being a mature technology [4]. The still low current densities, relatively large capital cost and the difficulties associated with energy harvesting/management are often cited as major challenges in their way towards practical application [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is not surprising that, in an effort to improve the commercial perspectives of BES, many researchers have come up with alternative designs that completely dispense with the membrane. Although many of them have proved to be successful in several fields of application such as organic and inorganic contamination removal [7,8] or energy production [9], the IEM becomes a critical element when the aim is to optimize energy efficiency (by avoiding oxygen and hydrogen crossover [4,6] ) or accomplish processes of industrial interest (nutrients recovery, microbial electrosynthesis or seawater desalination [10]). The application of several types of IEM such as anion exchange membranes (AEM), cation exchange membranes (CEM), microfiltration membrane, bipolar membrane and ultrafiltration membranes to BES has been extensively covered in the literature [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation